1987
DOI: 10.1001/archderm.1987.01660340093027
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Within a Southwestern Hispanic Population

Abstract: The New Mexico Melanoma Registry and New Mexico Tumor Registry identified 81 cases of melanoma involving the skin and mucous membranes of Hispanics. The clinical and pathologic characteristics of these tumors were compared with those observed in whites. The frequency of melanoma in Hispanics appears to be no more than a sixth of that observed in whites. Female patients were more prevalent within the Hispanic population. The median patient age at diagnosis was similar in Hispanics and whites. A much larger prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Hispanics are now the largest ethnic minority in the United States, comprising 17.8% of the population . Though data regarding stage at diagnosis and outcomes by ethnic group in pediatric melanoma are extremely limited, several studies inclusive of adults have reported that minorities including Hispanics with melanoma are more likely to present with regional or distant disease, further underscoring the need for public health strategies directly targeting Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics are now the largest ethnic minority in the United States, comprising 17.8% of the population . Though data regarding stage at diagnosis and outcomes by ethnic group in pediatric melanoma are extremely limited, several studies inclusive of adults have reported that minorities including Hispanics with melanoma are more likely to present with regional or distant disease, further underscoring the need for public health strategies directly targeting Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…26 AM has been reported to affect only 1%-3% of melanoma subtypes affecting non-Hispanics and white-skinned populations in the United States and Europe. 27,28 However, it is the most common clinical subtype in Asians, 24,29,30 Latin Americans, 28,31 and Africans, 27,32 with an incidence of 40%-71%. Furthermore, AM is often diagnosed at advanced stages; approximately 60% of the patients are diagnosed with stage II or higher disease at first examination.…”
Section: Acr Al Mel Anomamentioning
confidence: 99%
“…Due to its rarity the origin of oral melanomas and the risk factors are largely unknown. Certain races may be more commonly affected: the Japanese 12 , black Africans 13 , native Americans 14 and Hispanics 15 . A clearer correlation exists between melanomas of the oral mucosa and pre‐existing pigmentation.…”
Section: Discussionmentioning
confidence: 99%